Mitigating Floods for Managing Droughts through Aquifer Storage : An Examination of Two Complementary Approaches - Pavelic, Paul (World Bank, Washington, DC, 2020)
Interventions that are robust, cost effective, and scalable are in critical demand throughout South Asia to offset growing water scarcity and avert increasingly frequent water-related disasters. This case study presents two complementary forms of intervention that transform water hazards (floodwater) into a resource (groundwater) to boost agricultural productivity and enhance livelihoods. The first intervention, holiya, is simple and operated by individual farmers at the plot/farm scale to control local flooding in semiarid climates. The second is the underground transfer of floods for irrigation (UTFI) and operates at the village scale to offset seasonal floods from upstream in humid climates. Rapid assessments indicate that holiyas have been established at more than 300 sites across two districts in North Gujarat since the 1990s, extending the crop growing season and improving water quality. UTFI knowledge and experience has grown rapidly since implementation of a pilot trial in western Uttar Pradesh in 2015 and is now embedded within government programs with commitments for modest scaling up. Both approaches can help farmers redress the multiple impacts associated with floods, droughts, and groundwater overexploitation at a range of scales from farm plot to the river basin. The potential for wider uptake across South Asia depends on setting up demonstration sites beyond India and overcoming gaps in technical knowledge and institutional capacity.